A hydrogel-cement-based composite electrolyte, a preparation method and application thereof in supercapacitors
Patent Information
- Application Number
- CN202611498737.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的目的是提供一种水凝胶-水泥基复合电解质材料的制备方法,旨在解决现有技术中聚合物与水泥基体结合差、延缓水泥水化以及离子传输效率低的问题
(1)本发明打印的SPGF在不干扰水泥水化或破坏水化后形成的承载骨架的前提下,明显提升了水凝胶-水泥基复合电解质的离子电导率;
Smart Images

Figure CN123017751A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of capacitors, specifically to a hydrogel-cement-based composite electrolyte, its preparation method, and its application in supercapacitors. Background Technology
[0002] With the accelerating global energy transition, ensuring a stable supply and efficient utilization of renewable energy has become a key challenge. Buildings account for approximately 40% of global energy consumption, necessitating low-carbon energy supply strategies and efficient energy management technologies. In recent years, renewable energy technologies, represented by photovoltaics, have demonstrated significant potential in reducing building energy consumption. However, the inherent intermittency and weather dependence of solar and wind power hinder the real-time matching of renewable energy generation with building energy demand. Therefore, large-scale energy storage systems are crucial for improving the stability of building energy supply. Currently, building-side electrochemical energy storage mainly relies on external lithium-ion battery systems, which suffer from problems such as large space requirements, potential safety risks, limited long-term service stability, and poor compatibility with building structures. Against this backdrop, structural energy storage systems (SESSs) integrate energy storage functions into load-bearing building components, providing a low-cost, space-saving, and intrinsically safe alternative, thus laying the foundation for next-generation self-storage buildings.
[0003] Among various SESS (Separation Electrolyte System) designs, cement-based supercapacitors (CBSCs) have attracted increasing attention due to their scalability and low cost. However, hydration-induced densification of the pore structure hinders ion transport within the cement-based electrolyte / diaphragm (CBES), thus limiting the capacitance performance and cycling stability of CBSCs. To enhance the ion transport capability of CBES, researchers have widely adopted polymer doping (such as PAA, PAM, PVA, and PEO) and gas foaming techniques to improve pore connectivity. However, these methods inevitably interfere with the cement hydration process and compromise the structural integrity of the CBES, leading to a significant reduction in compressive strength. The ice template method, as an effective structural design strategy, can construct oriented ion transport channels, thereby improving ion conductivity while maintaining mechanical properties. However, when applied to thick-scale cement matrices, this method can cause uneven freezing and freeze-thaw damage, limiting its practical application. Therefore, it is crucial to develop a simple, scalable structure that can achieve efficient ion transport while maintaining structural integrity, which is essential for improving the ion transport performance of CBES.
[0004] 3D-printed hydrogel frameworks offer a promising approach to decoupling ion transport pathways from the intrinsic pore structure of cement. Pre-designed hydrogel frameworks can provide regular geometries and low-torsion ion transport channels, while also enabling scalable and low-cost fabrication. However, weak interfacial coupling between 3D-printed hydrogel frameworks and the cement matrix can lead to interfacial gaps, debonding, or structural discontinuities, thereby disrupting ion transport pathways, increasing interfacial resistance, and impairing stress transfer. Therefore, an ideal hydrogel framework should not only possess a low-torsion geometry but also establish a robust chemical coupling with the cement matrix. Sodium alginate (SA) is a natural anionic polysaccharide with abundant carboxylate (-COO) groups on its polymer chains. - SA can retain water and form continuous hydration domains that facilitate ion migration. Polyvinyl alcohol (PVA) further enhances the polymer network through hydrogen bonding interactions with SA, thereby improving the mechanical stability of the hydrogel. More importantly, the -COO group of SA... - The groups coordinate with multivalent metal cations to form a characteristic "egg-box" cross-linked network. Cement is rich in Ca... 2+ Possibly further cooperation with SA's COO - The groups coordinate at the interface between the hydrogel and cement. However, this is due to the presence of Ca... 2+ Whether induced interfacial crosslinking can effectively enhance the interfacial coupling of hydrogel-cement, and how it regulates the arrangement of polymer chains and ion transport behavior, remains unclear. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing a hydrogel-cement-based composite electrolyte material, aiming to solve the problems of poor bonding between the polymer and the cement matrix, delayed cement hydration, and low ion transport efficiency in existing technologies. The composite electrolyte material prepared by this invention achieves a strong interfacial bond between the hydrogel and cement, the hydrogel does not significantly affect cement hydration, and it can significantly improve the ion transport performance of the electrolyte.
[0006] The second objective of this invention is to provide an application of the hydrogel-cement-based composite electrolyte material prepared by the above preparation method in supercapacitors.
[0007] This invention is achieved through the following technical solution: This invention discloses a method for preparing a hydrogel-cement-based composite electrolyte, comprising the following steps: (1) Dissolve sodium alginate and polyvinyl alcohol powder in deionized water to obtain sodium alginate solution and polyvinyl alcohol solution respectively; mix sodium alginate solution and polyvinyl alcohol solution and stir to form a uniform mixed solution; (2) Add fumed silica to the mixed solution with continuous mechanical stirring until a non-collapsed slurry is formed; (3) The slurry was extruded layer by layer using a direct-write 3D printer to obtain a hydrogel grid framework with a regular structure, and then frozen to strengthen its structural stability. (4) Ordinary silicate cement slurry is poured into a mold, and the hydrogel grid frame is implanted into the cement slurry. After curing in a curing room, hydrogel-cement-based composite electrolyte is obtained.
[0008] Furthermore, the concentrations of sodium alginate solution and polyvinyl alcohol solution were 4 wt% and 16 wt%, respectively.
[0009] Furthermore, the mass ratio of fumed silica to sodium alginate is 2:1.
[0010] Furthermore, the printer's printing temperature is 22℃±3℃, the printer nozzle diameter is 0.8-1.5 mm, the printing speed is 5 mm / s, and the freezing temperature is -25 ~ -60℃.
[0011] Furthermore, in step (4), the amount of cement slurry added is 8-10 times the mass of the hydrogel grid frame.
[0012] Furthermore, in step (4), the water-cement ratio of the ordinary silicate cement slurry is 0.5-0.7, and SPGF is inserted into the cement slurry centered along the thickness direction of the mold.
[0013] The present invention also discloses the hydrogel-cement-based composite electrolyte prepared by the above preparation method.
[0014] This invention also discloses the application of hydrogel-cement-based composite electrolyte in supercapacitors.
[0015] In the above application, the positive electrode of the supercapacitor is made by coating a mixed slurry of activated carbon (NAC), acetylene black, and polyvinylidene fluoride (PVDF) onto a nickel foam (NF) current collector, wherein the mass ratio of NAC, acetylene black, and PVDF is 8:1:1. The coated positive electrode is then vacuum-dried at 40°C for 12 hours, and the loading of the positive electrode active material is 2.0 mg•cm³. -2 The negative electrode of the supercapacitor is a nickel foam loaded with ZnxMnO2 nanowires, and the loading of the negative electrode active material is 3.0 mg•cm³. -2 Before the hydrogel-cement-based composite electrolyte is fully cured, the positive and negative electrodes are symmetrically inserted on both sides of it, and the mass of the hydrogel-cement-based composite electrolyte is 4500 to 5500 times the loading of the positive electrode active material.
[0016] Beneficial effects (1) The SPGF printed by the present invention significantly improves the ionic conductivity of the hydrogel-cement-based composite electrolyte without interfering with cement hydration or destroying the supporting skeleton formed after hydration. (2) The Ca at the interface between the cement matrix and SPGF in this invention 2+ -COO - Coordination enhances interfacial coupling, significantly improving the mechanical properties of the composite electrolyte. Furthermore, Ca... 2+ -COO - Coordination promotes the orderly arrangement of polymer chains, thereby accelerating the migration of ions in the polymer network; (3) The present invention optimizes the structural morphology of cement-based composite materials at the microscale, and the preparation process is simple, the raw materials are widely available, environmentally friendly, and low in cost, which significantly improves the scalability of large-scale production. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the preparation and structural energy storage device of the hydrogel-cement-based composite electrolyte of the present invention; Figure 2 X-CT images of the hydrogel-cement-based composite electrolyte prepared in Example 1 of the present invention, wherein (a) is a three-dimensional PC-SPGF, (b) is a PC-SPGF tomographic section, (c) is the cement-based skeleton extracted after three-dimensional reconstruction, and (d) is the hydrogel grid frame extracted after three-dimensional reconstruction. Figure 3 The images shown are scanning electron microscope (SEM) images of embodiments and comparative examples 1 to 3 of the present invention, wherein (a) is the SEM of comparative example 1, (b) is the SEM of comparative example 2, (c) is the SEM of comparative example 3, and (d) is the SEM of the embodiment. Figure 4 The diagrams show the compressive strength and cumulative porosity of the embodiments and comparative examples 1-3 of the present invention at curing ages of 3 days, 7 days, and 28 days. (a) is the compressive strength diagram, and (b) is the cumulative porosity diagram. Figure 5 The electrochemical impedance spectroscopy (EIS) and ionic conductivity of the embodiments and comparative examples 1-3 of the present invention are shown. (a) is the EIS curve and (b) is the corresponding ionic conductivity. Figure 6 Cyclic voltammetry (CV) curves of the electrochemical performance tests of the embodiments and comparative examples 1-3 of this invention; Figure 7 The constant current charge-discharge curves (GCD) of the electrochemical performance tests of the embodiments and comparative examples 1-3 of this invention are shown. Figure 8 The electrochemical impedance spectroscopy (EIS) spectra of the embodiments and comparative examples 1-3 of this invention are shown. Figure 9 The figure shows the comprehensive test results of the electrochemical performance of the embodiments of the present invention, where (a) is the CV curve at different scan rates, (b) is the GCD curve at different current densities, and (c) is the sheet capacitance corresponding to different current densities. Figure 10 These are the long-term cycling stability test results of the embodiments and comparative examples 1-2 of the present invention; Figure 11 The diagram illustrates the practical application of the device in this invention driving commercial lighting devices of different power levels and smartphones. Detailed Implementation
[0018] The following is a detailed description of the accompanying drawings and embodiments of the present invention. These embodiments are implemented based on the technical solution of the present invention and provide specific implementation schemes and operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0019] like Figure 1 The diagram shows the preparation process and structural energy storage device of the hydrogel-cement-based composite electrolyte of the present invention.
[0020] Example 1 A method for preparing a hydrogel-cement-based composite electrolyte, comprising the following specific steps: (1) Dissolve 2 g of sodium alginate powder in 48 ml of deionized water at room temperature and stir slowly for 4 h to prepare a 4% sodium alginate solution. Add 8 g of polyvinyl alcohol to 42 ml of deionized water and stir rapidly in an oil bath at 90°C until completely dissolved to prepare a 16% polyvinyl alcohol solution. Mix 50 g each of the above sodium alginate solution and polyvinyl alcohol solution and stir until homogeneous to obtain a sodium alginate / polyvinyl alcohol mixed solution.
[0021] (2) Under continuous mechanical stirring, slowly add 4 g of fumed silica to the mixed solution and continue stirring until a printable slurry with good thixotropic properties is formed (a non-collapsed slurry visible to the naked eye is formed).
[0022] (3) The obtained slurry was loaded into a direct-write 3D printer equipped with a nozzle with a diameter of 1 mm, and printed layer by layer at a printing speed of 5 mm / s at room temperature to prepare a hydrogel skeleton SPGF with a grid framework structure. After printing, the SPGF was transferred to a freezer at -25 ℃ for freezing and shaping.
[0023] (4) Mix 20 g of ordinary silicate cement with 10 ml of deionized water and stir at a constant speed to prepare cement slurry. Pour the flowing cement slurry into polytetrafluoroethylene molds of 20×20×8 mm and 20×20×20 mm respectively. The former is used for electrochemical performance testing, and the latter is used for mechanical performance testing. Then, SPGF is implanted into the cement slurry along the thickness direction of the mold, and then placed in a curing chamber for 24 h. Among them, for the sample used for electrochemical testing, before curing, foamed nickel coated with activated carbon and foamed nickel coated with ZnxMnO2 are used as structural electrodes and inserted symmetrically on both sides of the mold parallel to SPGF to prepare cement-based supercapacitors. After curing, the sample is immersed in 2M KCl electrolyte solution for 24 h, and then electrochemical performance testing is carried out; when testing ionic conductivity, the above structural electrodes are replaced with stainless steel sheets and placed symmetrically on both sides of the mold in the same way.
[0024] Comparative Example 1 This comparative example provides a pure cement-based electrolyte and its application in a supercapacitor. The difference between this example and the previous one is that no hydrogel with a grid-like structure was added, and steps (1) to (3) in the previous example were not performed. The specific steps are as follows: 20 g of ordinary Portland cement was mixed with 10 ml of deionized water and stirred at a uniform speed to prepare cement slurry. The flowing cement slurry was poured into 20×20×8 mm and 20×20×20 mm polytetrafluoroethylene molds, respectively. The former was used for electrochemical performance testing, and the latter for mechanical performance testing. The molds were then placed in a curing chamber for 24 h. The samples used for electrochemical performance testing were coated with activated carbon-coated nickel foam and Zn-coated nickel foam before curing. x MnO2 nickel foam was inserted into both sides of the mold as structural electrodes to prepare a cement-based supercapacitor. After curing, the sample was immersed in 2M KCl electrolyte solution for 24 hours, followed by electrochemical performance testing. For ionic conductivity testing, the structural electrodes were replaced with stainless steel sheets and placed symmetrically on both sides of the mold in the same manner.
[0025] Comparative Example 2 This comparative example provides a hydrogel-cement-based composite electrolyte and its application in supercapacitors. The difference between this and the previous example is that an equal mass of the hydrogel solution with the grid-like structure is mixed with cement slurry. The specific steps are as follows: (1) Dissolve 2 g of sodium alginate powder in 48 ml of deionized water at room temperature and stir slowly for 4 h to prepare a 4% sodium alginate solution. Add 8 g of polyvinyl alcohol to 42 ml of deionized water and stir rapidly in an oil bath at 90°C until completely dissolved to prepare a 16% polyvinyl alcohol solution. Mix 50 g each of the above sodium alginate solution and polyvinyl alcohol solution and stir until homogeneous to obtain a sodium alginate / polyvinyl alcohol mixed solution.
[0026] (2) Mix 20 g of ordinary silicate cement, 10 ml of deionized water and 2 g of the sodium alginate / polyvinyl alcohol mixed solution, and stir at a constant speed to obtain cement slurry. The amount of sodium alginate / polyvinyl alcohol mixed solution added is consistent with the mass of the hydrogel grid frame obtained by direct writing 3D printing in the example.
[0027] (3) The flowing cement slurry was poured into 20×20×8 mm and 20×20×20 mm polytetrafluoroethylene molds, respectively. The former was used for electrochemical performance testing, and the latter for mechanical performance testing. The molds were then placed in a curing room for 24 hours. The samples used for electrochemical performance testing were coated with activated carbon-coated nickel foam and Zn-coated nickel foam before curing. x MnO2 nickel foam was inserted as structural electrodes on both sides of the mold to prepare a cement-based supercapacitor. After curing, the sample was immersed in a 2MKCl / 2M ZnSO4 electrolyte solution for 24 h, followed by electrochemical performance testing. For ionic conductivity testing, the structural electrodes were replaced with stainless steel sheets and placed symmetrically on both sides of the mold in the same manner.
[0028] Comparative Example 3 The preparation method is basically the same as that in the examples, except that polyvinyl alcohol is not added when preparing the hydrogel skeleton of the grid framework structure, while the other steps are the same.
[0029] Figure 2 The images shown are X-ray computed tomography (X-CT) images of the hydrogel-cement-based composite electrolyte prepared in Example 1. Figure 2 (a) shows the overall three-dimensional morphology of the composite electrolyte. Figure 2 (b) is a tomographic scan section that clearly shows the tight and continuous interface between the cement matrix (brown) and the hydrogel grid framework (blue), indicating that the two phases have good structural compatibility and interface integrity. Figure 2 (c) and Figure 2 (d) These are the cement matrix skeleton and hydrogel grid framework extracted after spatial reconstruction, respectively. Figure 2(c) As can be seen, the cement matrix is interconnected within the 3×3 grid units of the hydrogel lattice framework, forming a continuous three-dimensional load-bearing network, thus endowing the composite electrolyte with excellent mechanical load-bearing capacity. Meanwhile, as... Figure 2 As shown in (d), the continuous and interconnected independent hydrogel grid framework provides an ordered and efficient channel for ion transport, which is beneficial to improving the ion conduction performance of the electrolyte.
[0030] Figure 3 Scanning electron microscope (SEM) images of the embodiments and comparative examples 1-3 are shown, where (a) is the SEM image of comparative example 1, (b) is the SEM image of comparative example 2, (c) is the SEM image of comparative example 3, and (d) is the SEM image of the embodiment. As shown in comparative example 1, its microstructure exhibits randomly distributed disordered pores accompanied by flocculent CSH gel deposits. The pore channels lack orientation or interconnectivity, and this structural feature significantly inhibits ion transport efficiency. Compared to comparative example 1, comparative example 2 shows an increase in the number of pores, but the added pores still exist in a random and disordered form, failing to form an ordered interconnected network. In contrast, the SEM images of comparative example 3 and the embodiments show a continuous and oriented CSH gel network structure, indicating that the grid framework structure is beneficial for improving the tortuosity of the pore structure and promoting the regular and ordered arrangement of pores. It is particularly noteworthy that the CSH gel exhibits an "eggbox"-like configuration similar to calcium alginate, from which it can be inferred that Ca 2+ A cross-linking reaction occurred between the PC matrix and the sodium alginate (SA) polymer chain, which enhanced the interfacial bonding performance between the PC matrix and SPGF.
[0031] Figure 4 The compressive strength and cumulative porosity test results of Examples 1-3 and Comparative Examples 1-3 at curing ages of 3 days, 7 days, and 28 days are shown. Figure 4 (a) represents compressive strength. Figure 4 (b) is the total porosity diagram. (From...) Figure 4 (a) It can be seen that the compressive strength of Comparative Example 3 and the Example 2 was significantly higher than that of Comparative Example 2 throughout the entire curing period, which fully verifies the advantages of the hydrogel grid frame structure in terms of mechanical properties. This structure can effectively reduce the contact area between the hydrogel and cement particles, thereby significantly alleviating the hydration delay caused by the hydrogel encapsulating the cement particles. Figure 4(b) The microscopic mechanism of the strength difference was further revealed. Comparative Example 2, due to the mechanical blending of sodium alginate / polyvinyl alcohol mixed solution with cement slurry, introduced a large number of air bubbles during stirring, resulting in a total porosity as high as 43.39%, with a significant increase in the number of macropores larger than 10000 nm, which was the main reason for the significant decrease in its compressive strength. In contrast, the total porosity of the Example was significantly reduced to 31.95%, approaching the porosity level of Comparative Example 1 (29.29%). More notably, the Example achieved a compressive strength of 42.37 MPa at 28 days, only about 2% lower than Comparative Example 1, demonstrating excellent strength retention. These superior mechanical properties can be attributed to the following two synergistic mechanisms: on the one hand, the hydrogen bonding interaction between the polyvinyl alcohol and sodium alginate molecular chains significantly enhanced the structural stability of the hydrogel grid framework; on the other hand, and more crucially, at the cement-hydrogel interface, -COO - With Ca 2+ The coordination between them promotes the formation of CSH gels with an "egg-box" structure featuring interpenetrating network characteristics. This structure significantly enhances the interfacial bonding performance, thereby enabling the embodiments to obtain a denser microstructure and excellent mechanical properties.
[0032] Figure 5 The EIS curves and corresponding ionic conductivity of the examples and comparative examples 1-3 are shown. Figure 5 As shown in (a), the intersection of the EIS curve and the real axis (horizontal axis) reflects the volume resistance (R) of the electrolyte. b Compared to Comparative Examples 1-3, the bulk resistivity of the examples was significantly reduced, indicating that the hydrogel lattice framework structure is beneficial for reducing ion migration resistance and improving the ion conductivity of the electrolyte. Furthermore, the ionic conductivity calculated from EIS data is as follows: Figure 5 As shown in (b), the ionic conductivity of the embodiment is significantly better than that of the comparative examples, further verifying the significant advantage of the hydrogel grid framework structure in promoting rapid ion transport.
[0033] Figures 6 to 8 The figures show the CV curves, GCD curves, and EIS curves of the devices obtained in Examples 1-3 and Comparative Examples 1-3, respectively. Figure 6 As shown, the area of the CV curve of the device in the embodiment is significantly larger than that of comparative examples 1 to 3, indicating that it has a higher charge storage capacity at the same scan rate. Figure 7 The figure shows the GCD curves of the embodiment device and the devices in Comparative Examples 1-3. As can be seen from the figure, the device in the embodiment has the longest discharge time, and its surface capacitance is calculated to be 1624 mF•cm. -2The performance of Comparative Example 3 was significantly better than that of Comparative Examples 1-3. Furthermore, the discharge time of Comparative Example 3 was also significantly longer than that of Comparative Examples 1 and 2, further confirming the effect of the grid framework structure on improving electrochemical performance. Figure 8 The EIS curves for the devices in Examples 1-3 and Comparative Examples 1-3 are shown. The internal resistance (Rs) of the device in the Examples is 33.11 Ω, which is the lowest among all groups, indicating that it has the lowest charge transport resistance and the most favorable electrochemical reaction kinetics.
[0034] Figure 9 The following are the comprehensive electrochemical performance test results of the devices in the examples, where (a) is the CV curve at different scan rates, (b) is the GCD curve at different current densities, and (c) is the surface capacitance value at different current densities. Figure 9 As shown in (a), the scan rate increases from 5 to 100 mV•s -1 Within the specified range, the CV curves of the devices in the examples all maintained a relatively good rectangular shape, without obvious polarization or distortion, indicating that the devices possess excellent rate performance and fast ion response characteristics over a wide scan rate range. Figure 9 (b) As can be seen, under different current densities, the GCD curves of the devices in the embodiments all exhibit a well-symmetrical triangular shape with a small voltage drop, reflecting that the devices have low internal resistance and good structural stability. Further, as... Figure 9 As shown in (c), the surface capacitance value calculated from the GCD curve indicates that at a current density of 0.4 mA•cm -2 At that time, the surface capacitance of the device in the embodiment can reach 1916 mF•cm. -2 Even with the current density increased to 1.0 mA•cm -2 At that time, its surface capacitance remained at 863 mF•cm. -2 The high capacity retention rate fully demonstrates that the device can still achieve efficient charge storage under high current density operation.
[0035] Figure 10 The figures show the long-term cycling stability test results for the Example and Comparative Examples 1-2. As can be seen from the figures, the device in the Example exhibits the best capacity retention capability during cycling, significantly better than Comparative Examples 1 and 2. At 2 mA•cm -2At the specified current density, the device in the example retained 99.22% of its initial capacity after 2000 cycles, with a coulombic efficiency close to 100%. This indicates that the hydrogel lattice framework effectively shortens the ion diffusion path and reduces the interfacial contact resistance, thereby endowing the device with excellent cycling stability. In contrast, the device in Comparative Example 2 retained only 87.02% of its initial capacity under the same cycling conditions, showing significantly insufficient stability. The performance degradation of the device in Comparative Example 1 was particularly significant, with the capacity retention rate plummeting to 9.52% after 1000 cycles. This further indicates that poor pore connectivity and excessively high interfacial contact resistance are the main reasons for its deteriorated cycling stability.
[0036] Figure 11 The illustrations show practical applications of the device driving commercial lighting devices of different power levels and smartphones. Figure 11 As shown in (a), a single embodiment device can successfully light up an LED indicator, verifying its basic driving capability. Furthermore, when two embodiment devices are connected in series, the output voltage increases accordingly, sufficient to meet the turn-on voltage requirements of four different power LEDs (red, yellow, blue, and white), thereby achieving effective driving of these four types of LEDs. Figure 11 (b) indicates that the device can be flexibly adapted to commercial light sources of different power levels through a series connection. For example... Figure 11 (c) and Figure 11 As shown in (d), connecting the five devices of the embodiments in series significantly improves their output power, enabling them to stably drive commercial high-power LED bulbs and charge smartphones. These results fully demonstrate that the devices of the embodiments possess reliable power supply capabilities for driving commercial electronic devices, showcasing their promising application prospects in the field of power supply for portable electronic devices.
Claims
1. A method for preparing a hydrogel-cement-based composite electrolyte, characterized in that, Includes the following steps: (1) Dissolve sodium alginate and polyvinyl alcohol powder in deionized water to obtain sodium alginate solution and polyvinyl alcohol solution respectively; Sodium alginate solution and polyvinyl alcohol solution are mixed and stirred to form a homogeneous mixed solution; (2) Add fumed silica to the mixed solution under continuous mechanical stirring until a non-collapsed slurry is formed; (3) The slurry was extruded layer by layer using a direct-write 3D printer to obtain a regular sodium alginate / polyvinyl alcohol hydrogel grid framework, which was then frozen. (4) Ordinary silicate cement slurry is poured into a mold, and the hydrogel grid frame is implanted into the cement slurry. After curing in a curing room, hydrogel-cement-based composite electrolyte is obtained.
2. The method for preparing a hydrogel-cement-based composite electrolyte according to claim 1, characterized in that, The concentrations of sodium alginate solution and polyvinyl alcohol solution were 4 wt% and 16 wt%, respectively.
3. The method for preparing a hydrogel-cement-based composite electrolyte according to claim 1, characterized in that, The mass ratio of fumed silica to sodium alginate is 2:
1.
4. The method for preparing a hydrogel-cement-based composite electrolyte according to claim 1, characterized in that, The printer's printing temperature is 22℃±3℃, the printer nozzle diameter is 0.8-1.5mm, the printing speed is 5 mm / s, and the freezing temperature is -25 ~ -60℃.
5. The method for preparing a hydrogel-cement-based composite electrolyte according to claim 1, characterized in that, In step (4), the amount of cement slurry added is 8-10 times the mass of the hydrogel grid frame.
6. The method for preparing a hydrogel-cement-based composite electrolyte according to claim 1, characterized in that, In step (4), the water-cement ratio of ordinary silicate cement slurry is 0.5-0.7, and SPGF is inserted into the cement slurry centered along the thickness direction of the mold.
7. A hydrogel-cement-based composite electrolyte prepared by the preparation method according to any one of claims 1-6.
8. Application of a hydrogel-cement-based composite electrolyte in supercapacitors.
9. The application according to claim 8, characterized in that, The positive electrode of the supercapacitor is made by coating a nickel foam NF current collector with a mixed slurry of activated carbon (NAC), acetylene black, and polyvinylidene fluoride (PVDF), wherein the mass ratio of NAC, acetylene black, and PVDF is 8:1:
1. The coated positive electrode is then vacuum-dried at 40°C for 12 hours, and the loading of the positive electrode active material is 2.0 mg•cm³. -2 The negative electrode of the supercapacitor is a nickel foam loaded with ZnxMnO2 nanowires, and the loading of the negative electrode active material is 3.0 mg•cm³. -2 Before the hydrogel-cement-based composite electrolyte is fully cured, the positive and negative electrodes are symmetrically inserted on both sides of it, and the mass of the hydrogel-cement-based composite electrolyte is 4500-5500 times the loading of the positive electrode active material.